Portfolio Performance and Agency - Dybvig, Philip H.; Farnsworth, Heber K.; Carpenter, Jennifer N. (Review of Financial Studies, 2010)
In this paper we analyze the optimal contract for a portfolio manager who can exert effort to improve the quality of a private signal about future market prices. We assume complete markets over states distinguished by asset payoffs and place no restrictions on the form of the contract. We show that trading restrictions are essential because they prevent the manager from undoing the incentive effects of performance-based fees. We provide conditions under which simple benchmarking emerges as optimal compensation. Additional incentives to take risk are necessary when information can be manipulated or else the manager will understate information to offset the benchmarking.